Isolation, Characterization, and Immunogenicity of Mycoplasma pneumoniae Membranes - Pollack, J. Dennis (1970)
Membrane and soluble fractions of Mycoplasma pneumoniae, M. pulmonis, and M. laidlawii B were prepared by hypotonic lysis of whole cells. The membranes of M. pneumoniae and M. laidlawii B contained, as percentage of dry weight: 34 to 37% protein, 59 to 61% lipid, 3 to 4% carbohydrate as hexose, and 0.2% ribonucleic acid as ribose. NADH(2) and NADPH(2) oxidase activities were localized in the soluble fractions of M. pneumoniae and in the membrane fraction of M. laidlawii B. NADH(2) oxidase activity was localized in the soluble fraction of M. pulmonis. The lipids of M. pneumoniae were labeled when the organism was grown in the presence of either radioactive palmitic acid, oleic acid, cholesterol, or glycerol. The lipids were not labeled when grown in the presence of radioactive acetate. Palmitic acid radio-activity was found in neutral lipid, glycolipid, and phosphatide fractions. Immunodiffusion analyses of whole cells and membrane fractions demonstrated three reactive antigens. Two immunodiffusion antigens were localized in the membrane fraction. One of these apparently contains lipid. A third antigen, also considered lipoidal, was found in whole cells. Membrane and soluble fractions of M. pneumoniae were immunogenic. The immunogens eliciting metabolic-inhibiting antibodies were localized in the membrane. The membrane preparation also induced the formation of antibodies which fixed complement with an antigen extracted with lipid solvent. The soluble fraction contained a distinct immunogen which induces antibodies reactive in complement fixation with an antigen prepared by phenol extraction.